Fiscal Stimulus, Deposit Competition, and the Rise of Shadow Banking: Evidence from China - Acharya, Viral V.; Qian, Jun “QJ”; Su, Yang; Yang, Zhishu (Management Science, 2025)
The rise of shadow banking and attendant financial fragility in China can be traced to intensified deposit competition following the 2008–2009 global financial crisis (GFC). A large, state-owned bank’s deposits from cross-border money inflows fell significantly following the GFC, and it supported the government’s fiscal stimulus more aggressively than other large banks by issuing larger volumes of new loans. Small and medium-sized banks with more branch-level overlaps with this large bank relied more on shadow banking and issued more wealth management products (WMPs)—short-maturity, off-balance-sheet substitutes for deposits. Greater amounts of WMPs created rollover risks for the issuers, as reflected by higher yields on new WMPs, higher borrowing rates in the interbank market, and lower stock-market performance during liquidity stress. This paper was accepted by Victoria Ivashina, finance. Funding: This work was supported by the National Natural Science Foundation of China [Grants 71272024, 71972051, and 72071117]. Supplemental Material: The internet appendix and data files are available at https://doi.org/10.1287/mnsc.2023.04233 .